Martiniportella nom. nov., pro Notopleura Liebau, 1991 non Krauss, 1902 - Liebau, Alexander (Zootaxa, 2020)
Notopleura Liebau, 1991 (Crustacea, Ostracoda, Hemicytheridae) established as a subgenus of Thaerocythere Hazel, 1967 with the type species Thaerocythere (Notopleura) lusitanica Liebau, 1991, is a younger homonym of Notopleura Krauss, 1902 (Insecta, Orthoptera, Acrididae). It is here replaced by the new name Martiniportella, which refers to the harbour of São Martinho do Porto (Portugal), where the extant specimens came from.